MEDICAL STUDENTS’ MOTIVATION PROMOTION OF PROFESSIONAL COMPETENCE DEVELOPMENT - Koha, Aelita; Ivanova, Tatjana; Ivanova, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
When choosing the direction of education, it is important for a person or with the help of the given education he will be able to achieve the goals and ideals of his life, and realize his personality potential. The choice of a career, according to personality, determines success and successful professional performance. Medicine is an area that offers a wide range of opportunities to acquire a profession in various specializations. A successful study program for medical students is very closely related to motivation.Motivation is especially important in encouraging students to motivate the person to develop the chosen profession.Motivation involves mutual interconnection of beliefs, perceptions, values and interests. In the pedagogical process, this means that the need is the main motive for learning, so it is important to notice that one level of needs encourages learning. The main task of the study process is to develop students' knowledge and skills that are useful in further professional careersAim of the article: To study the motivation of students of medical college, the factors influencing it, which promote the development of professional competencesMethods: quantitative study method, research instrument-surveyMain results of the study on the factors of professional competence in the study process: competence of teachers (43%), content of the study program (21%), practical classes (24%).